2018
DOI: 10.1080/1061186x.2018.1435664
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles containing cross-linked hyaluronic acid particulates for control of degradation and swelling behaviour after administration into skin

Abstract: Microneedles (MN) containing cross-linked hyaluronic acid (X-linked HA) particulates were prepared to control the degradation and swelling behaviour after transdermal drug delivery. The X-linked HA particulates were prepared by cross-linking HA chains and then passing the particulates through a sieve. Then, microneedles were prepared by micromolding method. The rheological properties of X-linked HA were studied. The penetration success rate, mechanical failure and dissolution rate of microneedles containing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Cross-linking of HA may cause swelling and tailor the degradation or drug delivery [ 59 , 71 ]. Zhang et al [ 59 ] designed cross-linked HA MNs with 1,4-butanediol diglycidyl ether, enhancing the mechanical strength of MNs and lowering degradation of the matrix, thus, an excellent prospect for prolonged drug delivery.…”
Section: Results Of Prisma Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-linking of HA may cause swelling and tailor the degradation or drug delivery [ 59 , 71 ]. Zhang et al [ 59 ] designed cross-linked HA MNs with 1,4-butanediol diglycidyl ether, enhancing the mechanical strength of MNs and lowering degradation of the matrix, thus, an excellent prospect for prolonged drug delivery.…”
Section: Results Of Prisma Analysismentioning
confidence: 99%
“…Cross-linking of HA may cause swelling and tailor the degradation or drug delivery [59,71]. Zhang et al [59] In vivo studies revealed that the release of the drug was achieved within 5 mins after insertion, and microarrays were completely dissolved within 15 mins in the skin [79].…”
Section: Carbohydrate-based Microneedlesmentioning
confidence: 99%
“…compared the penetration success, mechanical strength, and dissolution rate of pure HA MNP and x-HA MNP. The latter was found to degrade more slowly than the former, but completely within 200 hours (Choi et al., 2018b ). And the addition of cross-linking agent resulted in a strong elastic behavior of the skin after drug administration.…”
Section: Types Of Ha Mnpmentioning
confidence: 99%
“…Choi et al fabricated microneedles comprising cross-linked HA by micromolding strategy 30 . HA was cross-linked using 1,4butanediol diglycidylether.…”
Section: Ha Based Transdermal Microneedles Patchesmentioning
confidence: 99%